Respuestas
Respuesta dada por:
2
Respuesta:
43585
Explicación paso a paso:
benjamincelismunoz20:
maria como jajaj?
Respuesta dada por:
1
Respuesta:
Es -29
Explicación paso a paso:
- {3 - 8 [ 4 - 3 + (5 + 2 - 10) - (4 - 5) - 3] + 4 - 8} + 2
= -(3+-8(4+-3+1(5+2+-10)+-1(4+-5)+-3)+4+-8)+2
=-(3+-8(4+-3+1-3+-1(4+-5)+-3)+4+-8)+2
=-(3+-8(4+-3+-3+-1-1+-3)+4+-8)+2
= -(3+-8(4+-3+-3+1+-3)+4+-8)+2
= -(3+-8(4+-3+-3+-2)+4+-8)+2
= -(3+-8(4+-3+-5)+4+-8)+2
=-(3+-8-4+4+-8)+2
= -(3+-8-4+4+-8)+2
= -(3+32+4+-8)+2
= -(3+32+-4)+2
=-(3+28)+2
= -31+2
= -29
Preguntas similares
hace 3 años
hace 3 años
hace 6 años
hace 6 años
hace 8 años